Hubungan Dukungan Sosial dengan Self Esteem pada Pasien Tb Paru di Puskesmas Pekauman Kota Banjarmasin - Ardianto Priwijaya; Angga Irawan; Onieqie Ayu Dhea Manto (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Pulmonary tuberculosis causes physical and psychological impacts, if there is no good coping mechanism and social support, it can cause self-esteem to be disturbed. The purpose of this study was to determine the relationship between social support and self-esteem in pulmonary TB patients at the Pekauman Health Center, Banjarmasin City. The type of research is descriptive correlation with a cross-sectional design on 36 samples of pulmonary TB patients at the Pekauman Health Center, Banjarmasin City with a total sampling technique. This study used primary data obtained from questionnaires. Data analysis used univariate and bivariate Chi Square. The study found that respondents' social support was low 38.9%, moderate social support 30.6% and high social support 30.6% while low self-esteem was 50%, moderate self-esteem 27.8% and high self-esteem 22.2%. Chi square analysis obtained a p-value of 0.000 (<0.05), meaning that there was a relationship between social support and self-esteem in pulmonary TB patients at the Pekauman Health Center, Banjarmasin City.